1987
DOI: 10.1901/jeab.1987.48-61
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus‐ and Pellet‐induced Drinking During a Successive Discrimination

Abstract: In three experiments, interim water drinking was examined in rats exposed to a multiple schedule whose two components were extinction and a variable-time 30-s schedule of food delivery. Two different drinking patterns were observed in Experiment 1. Pellet-induced drinking, characterized by high rates of postpellet drinking in the variable-time component, with little or no drinking in extinction, occurred when the acquisition of stable postpellet drinking preceded discrimination training. Stimulus-induced drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…When milk delivery was terminated, responding of both strains underwent extinction. For both strains, suspension of the reinforcement contingency resulted in increased levels of responding or extinction bursts (Minor, 1987; Weissman, 1959) early during the session, followed by a clear decline in responding across the remainder of the session. By the end of the session, response rates were reduced significantly compared to those maintained by the operant contingency.…”
Section: Discussionmentioning
confidence: 99%
“…When milk delivery was terminated, responding of both strains underwent extinction. For both strains, suspension of the reinforcement contingency resulted in increased levels of responding or extinction bursts (Minor, 1987; Weissman, 1959) early during the session, followed by a clear decline in responding across the remainder of the session. By the end of the session, response rates were reduced significantly compared to those maintained by the operant contingency.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, these results highlight the difficulties of inferring the underlying cause of behavior from its time of occurrence in the IRI (Falk, 1971;Staddon, 1977). It seems worthwhile to investigate the source of control for other schedule-induced, adjunctive, or interim behaviors in designs that permit the differentiation of conditioned and unconditioned behavior (see, e.g., Minor, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the increased activity may be a direct consequence of US presentations. Responses may be directly elicited by the US, and repeated US presentations have been shown to increase a variety of scheduleinduced or adjunctive behaviors (Falk, 1971;Staddon, 1977), elicited by discriminable periods of low reinforcement probability (Minor, 1987;Staddon & Simmelhag, 1971), and/or the cumulation of elicited arousal across trials (Killeen, Hanson, & Osbome, 1979). However, in the usual situations in which these activities have been observed (during training sessions), ODe cannot distinguish between activities that are elicited by the preceding food presentation and activities that occur in anticipation of the next one.…”
Section: Methodsmentioning
confidence: 99%
“…A number of investigators (Lashley & Rosellini, 1980;Millenson, Allen, & Pinker, 1977;Minor, 1987;Minor & Coulter, 1982;Staddon, 1977) have proposed that schedule-induced behaviors may be particularly likely to be displayed in the presence of stimuli, including exteroceptive cues, associated with a reduction in the probability of reinforcement. While a number of investigators have reported evidence of schedule-induced drinking during the S-component of multiple schedules employing food reinforcers (Dougan, McSweeney, & Farmer, 1985;Keehn & Colotla, 1971;Minor, 1987;Minor & Coulter, 1982), other investigators have failed to obtain evidence of such an effect (cf. Hamm, Porter, & Kaempf, 1981;Jacquet, 1972; for reviews see Lashley & Rosellini, 1987;Minor, 1987;Porter & Hamm, 1984).…”
Section: Phase Onementioning
confidence: 99%
“…While a number of investigators have reported evidence of schedule-induced drinking during the S-component of multiple schedules employing food reinforcers (Dougan, McSweeney, & Farmer, 1985;Keehn & Colotla, 1971;Minor, 1987;Minor & Coulter, 1982), other investigators have failed to obtain evidence of such an effect (cf. Hamm, Porter, & Kaempf, 1981;Jacquet, 1972; for reviews see Lashley & Rosellini, 1987;Minor, 1987;Porter & Hamm, 1984).…”
Section: Phase Onementioning
confidence: 99%